PFAS Experts Symposium 2: Key advances in poly‐ and perfluoroalkyl characterization, fate, and transport. Issue 1 (3rd January 2022) - Bryant, J. Daniel; Anderson, Richard; Bolyard, Stephanie C.; Bradburne, J. Tim; Brusseau, Mark L.; Carey, Grant; Chiang, Dora; Gwinn, Rosa; Hoye, Brian R.; Maher, Thomas L.; McGrath, Angus E.; Schroeder, Matthew; et al.
Abstract: The PFAS Experts Symposium 2, held virtually from June 29 to July 1, 2021, brought together experts from a wide range of disciplines to discuss recent advances and current thinking regarding per‐ and polyfluoroalkyl substances (PFAS) in the environment. Within the general areas of characterization and fate and transport, three topics were identified that are of relevance for site assessment and remediation, and for which our understanding has greatly expanded or evolved since the first PFAS Experts Symposium in 2019: the significance of background PFAS sources to the environment, the relevance and use of nonselective analytes in site characterization, and PFAS retention in soil and the vadose zone. PFAS have been identified in shallow soil nearly worldwide, including far from known or suspected PFAS sources, and PFAS detected in soil and groundwater at sites under environmental investigation may not reflect on‐site sources. New advances in nonselective preparation and analytical methods offer promise for more rapid site screening and for assessing the presence and relative concentration of nontargeted PFAS. We also now recognize that a wide range of soil characteristics and processes may affect PFAS sorption and desorption from soil, and ultimately influence PFAS mobility and concentration in groundwater and surface water.